Towards Conflict Transformation and Management skills’ training in Zimbabwean Primary School Teacher Education for effective Teaching, Learning and Peace in Zimbabwean Primary School: A Case Study of Mkoba Teachers’ Training College. - Saiden, Thondhlana (Advances in Social Sciences Research Journal, 2017)
The purpose of education is to address societal problems. Conflicts in schools like in any organization are inevitable. If these are not managed and transformed they affect negatively learning, teaching and peace in schools. There is therefore, need to manage and transform conflicts in schools. Imparting conflict resolution skills is both imperative and necessary in schools and teacher educational colleges. The study was sparked off by a realization that conflict management and transformation was downplayed in teacher educational colleges resulting in the absence of programmes aimed at addressing this very important area. The study focused on establishing the curriculum that was to be exposed to student teachers in teacher educational colleges in a bid that these students could subsequently impact the knowledge, skills and attitudes into their pupils when they completed their training. The sample for the study was 20 student teachers and 10 teacher educational college lecturers who were purposively chosen. A qualitative research methodology was employed. A case study design was adopted. The major findings of the study were that the teacher educational college curriculum covers much of the areas on conflict resolution, the teacher education curriculum however, does not cover areas such as mediation, ethics and good manners, interdependence of nations, bullying, cooperative learning academic controversy, methods used in teaching students adequately, assessment was largely norm-referenced and schools did not do areas of the Health and Life skills as in colleges. The study recommended that the teacher educational college curriculum was to cover left out areas, assessment was to be criterion-referenced, the school curriculum was to be in sync with the teacher educational curriculum.